(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
Nowadays automation has an important place in metrology, because allows to improve the quality of the measurement results. This paper presents the design, construction and automation of a system for calibration of weights between 100 g and 500 g, which consists of an artificial vision system employed to determinate the standard and test masses. A rail system guided by a control loop performs weighting and comparison cycles; the data obtained is exported to a spreadsheet program in such way that at the end of the process it is possible to directly print the calibration certificate for each weight. The system reduces some errors generated by handling of the operators, such as eccentricity (incorrect weight placement), repeatability (force used to place the weights on the scale) and heat transfer from operator to weights. The system construction has been made inside of a climatic chamber, thereby the problems caused by temperature and humidity changes will be reduce significantly, decreasing the uncertainty by air buoyancy. This system offers an alternative to calibration systems used today, which improves weight calibration (measurement, accuracy and precision), decrease operative time, acquisition and maintenance costs because it reduces the space to be controlled and automates most of the manual process